Military and political importance of railway in the Great Patriotic War - Gorbunov Aleksander Aleksandrovich; Kretov Boris Ivanovich (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2013)
The Great Patriotic War became one of the most difficult periods in the history of the country. The Soviet Government constantly paid great attention to the defense of our motherland and highlighted railways. Railway transport was pointed out to be the most significant material factor of the war. Only welldeveloped, precisely and unbroken operating transport is enable to implement build-up of troops, to keep their high maneuverability, to provide in time the front with all necessary facilities, to meet the requirements of the national economy and population in transportation, to strengthen unity of front and rear.